Policy evaluation and performance assessment for sustainable urbanization: a study of selected city corporations in Bangladesh - Hossain, Imran; Haque, A. K. M. Mahmudul; Ullah, S. M. Akram (Frontiers in Sustainable Cities, 2024)
Bangladesh is going through an unprecedented period of urban growth, and its cities are having to deal with rising service, housing, and infrastructural needs. It is critical to comprehend how urban government promotes sustainable development as the nation struggles with the intricacies of urbanization. This study aims to investigate how urban governance impacts sustainable urbanization at the city corporation level in Bangladesh, focusing on Goal 11 of the Sustainable Development Agenda, which is "sustainable cities and communities."The study selected Rajshahi and Gazipur City Corporations as case studies and employed Principal Component Analysis (PCA) and descriptive statistics methods to gather data from primary and secondary sources. The findings of the study reveal gaps in urban governance, highlighting inconsistencies between the expectations of stakeholders and the reality on the ground. Stakeholders express high expectations for housing access, infrastructure development, disaster management, transportation, and environmental sustainability, but the current state falls short in several areas. Further, the study proposes several recommendations to enhance urban governance, including fostering participatory approaches, ensuring sufficient budget allocation for infrastructure development, addressing housing challenges, enhancing women's safety in transportation, and strengthening disaster management systems.